ANALISIS DEFORMASI MAKSIMUM BANGUNAN TINGGI DENGAN SISTEM OUTRIGGER TERHADAP BEBAN ANGIN - Resti Nur Arini; Fadli Kurnia; Dwi Ariyani; Soni (Jurnal Infrastruktur, 2020)
Outrigger structural systems are quite effective using the lateral loads on tall buildings, one of the main benefits of utilization outrigger is that it can reduce deformation and the danger of inter-story drift caused by lateral loads acting on the building. In this case, wind loads will be viewed as a lateral load because the wind load acting on tall buildings can also cause deformation of the building. The implementation of the outrigger system is viewed from different positions to see the deformation that occurs and the placement of the maximum location. The results of the analysis of wind loads reviewed on these buildings have proven that the use of outriggers in buildings can reduce displacement by 19.58%, and inter-storey drifts by 13.24%, which is applied in a position of ½ of the building height. The optimum location of the outrigger installation can also be determined by calculating the analysis of the maximum deflection that occurs on the 40th floor.